Velocity and Motion Control of a Self-Balancing Vehicle Based on a Cascade Control Strategy. (1st June 2016) - Velazquez, Miguel; Cruz, David; Garcia, Salatiel; Bandala, Manuel
This paper presents balancing, velocity and motion control of a self-balancing vehicle. A cascade controller is implemented for both balancing control and angular velocity control. This controller is tested in simulations using a proposed mathematical model of the system. Motion control is achieved based on the kinematics of the robot. Control hardware is designed and integrated to implement the proposed controllers. Pitch is kept under 1° from the equilibrium position with no external disturbances. The linear cascade control is able to handle slight changes in the system dynamics, such as in the centre of mass and the slope on an inclined surface.